Quantification of lactate enantiomers in human sweat samples using two-dimensional liquid chromatography - Kazushi Mori; Makoto Tsunoda (Journal of Chromatography Open)
Lactate (LA) is primarily produced by the reduction of pyruvate in the human body and is crucial for energy production via anaerobic glycolysis. Although the D-LA concentration is considerably lower than that of L-LA, a significant increase in D-LA concentration alone has been reported in some diseases. Quantifying LA enantiomers in human biofluids has the potential for disease diagnosis. Sweat has recently been recognized as a novel biological alternative to blood because it can be sampled non-invasively. Therefore, in this study, heart-cutting two-dimensional liquid chromatography (2D-LC) using a highly sensitive fluorescence detection method was developed for the analysis of LA enantiomers in small amounts of human sweat. LA was derivatized with 4-nitro-7-piperazino-2,1,3-benzoxadiazole (NBD-PZ) and separated from endogenous compounds using an octadecyl silica column in the first dimension. Subsequently, the NBD-PZ-LA peak was fractionated and enantiomerically separated in the second dimension on a chiral column. Sufficient linearities (R² > 0.999) were observed in the ranges of 1–100 and 10–1000 µM for NBD-PZ-D-LA and NBD-PZ-L-LA, respectively. The corresponding limits of quantification were 0.97 and 1.12 µM. The precision values were 1.04 %–12.03 %, and the accuracies were 85.6 %–100.4 %. The developed method was successfully applied to ∼5 µL of human sweat collected from five healthy subjects. The concentrations of D-LA and L-LA in sweat were 30.29 ± 20.18 µM and 23.69 ± 12.15 mM, respectively. The developed 2D-LC system should be clinically applicable to LA enantiomer analysis in human sweat as a non-invasive biomarker.